2007
DOI: 10.1007/s00702-007-0625-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of vagus activity in the brainstem – a methodological progress towards earlier diagnosis of dementias?

Abstract: In Alzheimer's disease (AD), mild functional disturbances should precede gross structural damage and even more clinical symptoms, possibly by decades. Moreover, alterations in the brainstem are supposed to occur earlier as cortical affections. Based on these considerations, we developed a new method aiming at the measurement of vagal brainstem functioning by means of evoked potentials after electrical stimulation of the cutaneous representation of the vagus nerve in the external auditory channel. In the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 49 publications
5
38
0
Order By: Relevance
“…This finding is in line with previous observations as well as a priori hypotheses: the results of prolonged VSEP in patients with AD in comparison to HC as reported previously [27] could be confirmed by a separate sample of subjects and up-to-date technical equipment. In accordance with previous data, in both bipolar recordings of stimulation on the right side (C4-F4 and FZ-F4) a delay of EP could be shown for patients with AD ( fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding is in line with previous observations as well as a priori hypotheses: the results of prolonged VSEP in patients with AD in comparison to HC as reported previously [27] could be confirmed by a separate sample of subjects and up-to-date technical equipment. In accordance with previous data, in both bipolar recordings of stimulation on the right side (C4-F4 and FZ-F4) a delay of EP could be shown for patients with AD ( fig.…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with our previous studies [26,27], the following data refers to the recordings of the right channels during stimulation at the right tragus. An EP with unique and clearly identifiable peaks (P1, N1, and P2) was observed in 20 out of 27 HC with location, shape, latencies, and amplitudes well in line with cited studies.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Likewise, drug effects cannot be ruled out. Finally, a previous study demonstrated latency prolongation in Alzheimer patients [10]. Thus, lack of formal assessment of cognitive impairment in our study may have led to inclusion of subjects with an Alzheimer comorbidity confounding the results.…”
Section: Dear Sirsmentioning
confidence: 76%
“…Vagus somatosensory-evoked potentials (VSEP) were proposed for clinical practice as a possible means for the early and differential diagnosis for neurodegenerative diseases and the functional assessment of specific brainstem nuclei in those diseases [1,2]. The principle of VSEP is based on the electrical stimulation of the auricular branch of the vagus nerve (ABVN [3]) showing afferences not only to trigeminal nuclei, but also to the solitary tract nucleus as a central afference of the main vagus trunk [4].…”
Section: Introductionmentioning
confidence: 99%